Selenium-containing polysaccharide from Spirulina platensis alleviates Cd-induced toxicity in mice by inhibiting liver inflammation mediated by gut microbiota - Zhou, Ning; Long, Hairong; Yu, Lian; Xia, Xianghua; Zhu, Zhenjun; Liu, Xiaoling (Frontiers in Nutrition, 2022)
Selenium-containing polysaccharide from Spirulina platensis (Se-SPP) has been demonstrated to help in inhibiting cadmium-induced injury in mice, but the underlying mechanism has not been determined. This study aimed to investigate the beneficial effects of Se-SPP on alleviating Cd-induced toxicity in mice by targeting liver inflammatory and gut microbiota. Se-SPP supplementation for 28 days in Cd-induced toxic mice significantly mitigated liver pathological damage and inflammation, which was correlated to the upregulation of antioxidant enzyme activity. Furthermore, Se-SPP effectively restored Cd-induced disruption of the intestinal barrier compared to model group, as indicated by the depletion of Muribaculaceae and the enrichment of Ruminococcaceae. Spearman's correlation analysis revealed that the Se-SPP-altered microbes were highly correlated with inflammation-related indexes in Cd-induced toxic mice. Noteworthily, the modulation of Se-SPP on the Ruminococcaceae population contributed to the improvement of Cd-induced inflammation-related diseases by downregulating the tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ) in the liver. These findings suggested that Se-SPP may act as prebiotics for ameliorating Cd-induced toxicity in mice by inhibiting liver inflammation mediated by gut microbiota, and target-specific microbiota of Cd-induced inflammation-related diseases deserve further attention.